ChemInform Abstract: Four New Ginkgolic Acids from Ginkgo biloba. Issue 51 (23rd December 2014) - Deguchi, Jun; Hasegawa, Yuki; Takagi, Ayana; Kutsukake, Shihoko; Kono, Mizue; Hirasawa, Yusuke; Wong, Chin Piow; Kaneda, Toshio; Morita, Hiroshi
Abstract The compounds (I) and (II) are examined as an inseparable mixture of isomers and are ultimately defined by total synthesis.